2018
DOI: 10.1021/acsomega.8b01195
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Charge Transport and Increased Active Sites on α-Fe2O3 (110) Nanorod Surface Containing Oxygen Vacancies for Improved Solar Water Oxidation Performance

Abstract: The effect of oxygen vacancies (V O ) on α-Fe 2 O 3 (110) facet on the performance of photoelectrochemical (PEC) water splitting is researched by both experiments and density functional theory (DFT) calculations. The experimental results manifest that the enhancement in photocurrent density by the presence of V O is related with increased charge separation and charge-transfer efficiencies. The electrochemical analysis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 57 publications
(83 reference statements)
2
20
0
Order By: Relevance
“…Both oxygen vacancies ( V O s), the main native point defects in hematite, and dislocations lead to broadening of the Raman lines. , However, in the case of dislocations, the peaks shift toward higher frequencies with respect to defect-free hematite and the shift increases with increasing dislocation density . On the contrary, in the case of V O s, the self-doping of α-Fe 2 O 3 surface due to the close Fe 2+ -sites , causes the peaks to shift toward lower frequencies …”
Section: Resultsmentioning
confidence: 99%
“…Both oxygen vacancies ( V O s), the main native point defects in hematite, and dislocations lead to broadening of the Raman lines. , However, in the case of dislocations, the peaks shift toward higher frequencies with respect to defect-free hematite and the shift increases with increasing dislocation density . On the contrary, in the case of V O s, the self-doping of α-Fe 2 O 3 surface due to the close Fe 2+ -sites , causes the peaks to shift toward lower frequencies …”
Section: Resultsmentioning
confidence: 99%
“…The enhanced performance of hematite photoanodes aer N 2 treatments has also been reported. 93 The experimental results showed that the enhanced performance induced by the presence of OVs was related to an increase of both charge separation and charge transfer efficiencies. Combining these experimental results with DFT calculations, it was found that the enhanced charge separation was achieved by the increased electron density combined with a decrease in the surface potential which improves the hole transport from the bulk to the (110) surface.…”
Section: Hematite Fe 2 Omentioning
confidence: 97%
“…[18][19][20] Alternatively, effective light absorption with undoubtedly decreased recombination and improved photocatalytic performance through defect engineering have been reported. [21,22] Defects in semiconductors greatly alter carrier concentration and interface reaction affecting the overall process efficiency of a photocatalyst. Thus, defects are the most frequently investigated scenario for tuning the properties of photocatalyst.…”
mentioning
confidence: 99%